PENGARUH TEMPERATUR DAN BENTUK TAKIKAN TERHADAP KEKUATAN IMPAK LOGAM - Zuchry M, Muhammad (MEKTEK, 2012)
The ability of a material in its use can be influenced by various factors including the temperature. The lower the temperature of the material will be more brittle and conversely the higher the temperature the material will be more resilient, and toughness will also be affected by the presence of defects in material such as cracks, corrosion, holes, etc. and. Impact test is one way to analyze and know the mechanical properties of the material, and the impact test will be the extent to which teperatur and can affect the notch toughness and ductility of the material. It is important to beÂ can know how a material will be feasible or not to be used